Elucidating Coastal Foredune Ecomorphodynamics in the U.S. Pacific Northwest via Bayesian Networks. Issue 7 (5th July 2019) - Biel, R. G.; Hacker, S. D.; Ruggiero, P.
Abstract: As sea level rise and possible changes in storminess threaten coastal communities and infrastructure, the capacity for foredunes to provide protection depends on their geomorphology, which is determined by interactions between physical beach processes and vegetation. Here we use descriptive Bayesian network analyses to examine how sediment supply, beach characteristics, and two species of beachgrass ( Ammophila arenaria and Ammophila breviligulata ) alter foredune morphology and patterns of sand accretion on U.S. Pacific Northwest foredunes. We show that sediment supply and beach type primarily determine foredune morphology. Beachgrass density also influences foredune shape, but its effects differ among species: increasing density of A. arenaria was associated with steeper sloping dunes, whereas increasing density of A. breviligulata was associated with wider, more shallow sloping dunes. An examination of the change in foredune morphology over a 2‐year period found sand accretion was most strongly influenced by species‐specific patterns of vegetation growth and beach type. Specifically, A. breviligulata exhibited more lateral growth, resulting in greater sand accretion at the seaward margin of the foredune. In contrast, A. arenaria exhibited little lateral growth, resulting in comparatively more sand accretion near the foredune crest. Consequently, growth form‐generated sand accretion patterns resulted in steep, narrow A. arenaria ‐dominated foredunes and shallow‐sloping, wider A. breviligulata ‐dominated foredunes. These results illustrate that vegetation density and patterns of growth influence foredune morphology and its changes over time. Key Points: Sediment supply and beach type influence both foredune morphology and rates of foredune change Foredune morphology and rates of foredune change are influenced by species‐specific beachgrass density and growth form patterns Foredune ecomorphodynamics differ among the beachgrass congeners, Ammophila arenaria and Ammophila breviligulata